2020
DOI: 10.1111/his.14118
|View full text |Cite
|
Sign up to set email alerts
|

Sry‐related high‐mobility‐group/HMG box 10 (SOX10) as a sensitive marker for triple‐negative breast cancer

Abstract: Sry-related high-mobility-group/HMG box 10 (SOX10) as a sensitive marker for triple-negative breast cancer Aims: Confirmation of a breast origin for triple-negative breast cancer (TNBC) is sometimes problematic. The traditional breast markers GATA-binding protein 3 (GATA3), mammaglobin (MGB) and gross cystic disease fluid protein 15 (GCDFP15) have shown limitations in identifying TNBC. Here, we aimed to examine the diagnostic potential of the newly proposed TNBC marker, Sry-related high-mobility-group/HMG box … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 43 publications
(186 reference statements)
6
22
1
1
Order By: Relevance
“…More recently, GATA3 staining has been shown to be an effective and sensitive complementary marker when attempting to trace the origin of metastatic breast cancer, 8,14,15 and was also strongly positive in our case.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…More recently, GATA3 staining has been shown to be an effective and sensitive complementary marker when attempting to trace the origin of metastatic breast cancer, 8,14,15 and was also strongly positive in our case.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, the lymph node showed a more even distribution of cells, and occasional scattered calcifications that are more commonly seen in breast carcinomas. More recently, GATA3 staining has been shown to be an effective and sensitive complementary marker when attempting to trace the origin of metastatic breast cancer, 8,14,15 and was also strongly positive in our case.…”
Section: Discussionsupporting
confidence: 62%
“… 30 Moreover, Jamidi et al indicated that SOX10 protein has high level in BRCA, which could be a sensitive marker for BRCA patients. 31 The main reason might lie in the existence of some post-transcriptional regulation for SOX10 in BLCA and BRCA. There are few studies on SOX10 in other tumors, so the function and mechanism of SOX10 are unclear in COAD, ESCA, PRAD, READ and TGCT.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, SOX-10 has been reported to be commonly positive in GATA3-negative TNBC metastases [ 28 ]. The combination of SOX-10 and GATA3 yielded a sensitivity of about 60% for the identification of TNBC in a recent study investigating >1800 cases [ 29 ]. The combination of GATA3 and SOX-10 staining has been proven to be useful to identify mammary origin in several previous studies [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%